Students' Alternative Concept on the Topic of Energy in Life - Dewi, Safira Permata; Saparini, Saparini; Destiansari, Elvira; Anjelina, Ersa Lois; Setiani, Liska (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2024)
This research aims to get the alternative concepts of students regarding the concept of energy in life using integrative instruments. The concept of energy in life consists of two topics, photosynthesis and cellular respiration. A sample of 375 students was established using the random sampling technique. They were from 14 junior high schools in Palembang City using the stratified cluster sampling. The instrument used consists of 30 free-response. The results of this research show that students understand the concept that photosynthesis can only occur in leaves (23.70%) and takes place during the day (33%) by utilizing oxygen (25.80%) while existing sunlight functions as the lighting in the photosynthesis process (17.20%) and chlorophyll plays a role in providing coloring to plants (16.50%). On the topic of cellular respiration, students understand that cellular respiration is an activity for the formation and addition of energy in living things (30.40%) and can occur in all parts of the body of living things (31.30%). Both ordinary cellular respiration and fermentation are carried out utilizing oxygen (72.40%). The results show that the alternative concepts possessed by students are very diverse with basic concepts, even though these basic concepts have been studied at previous levels of education.